Dynamic-Mechanical Behaviour of Bio-composites. (2016) - Durante, M.; Langella, A.; Formisano, A.; Boccarusso, L.; Carrino, L.
Abstract: PLA-hemp bio-composites with different reinforcement content were manufactured by compression moulding process. Both flexural and impact properties were investigated and compared to the unreinforced polymer. In addition, also the creep behaviour adopting the Arrhenius theory was determined, in order to better understand the industrial application limits of PLA reinforced by natural fibres. For this purpose, DMA tests were carried out, in order to evaluate the activation energy and to apply the Time-Temperature Superposition model to the compliance curves obtained by short-time creep tests.